A crisis communication network based on embodied conversational agents system with mobile services - Goh, Ong Sing; Ardil, Cemal; Fung, Chun Che; Wong, Kok Wai; Depickere, Arnold (World Academy of Science, Engineering and Technology, 2007)
In this paper, we proposed a new framework to incorporate an intelligent agent software robot into a crisis communication portal (CCNet) in order to send alert news to subscribed users via email and other mobile services such as Short Message Service (SMS), Multimedia Messaging Service (MMS) and General Packet Radio Services (GPRS). The content on the mobile services can be delivered either through mobile phone or Personal Digital Assistance (PDA). This research has shown that with our proposed framework, the embodied conversation agents system can handle questions intelligently with our multilayer architecture. At the same time, the extended framework can take care of delivery content through a more humanoid interface on mobile devices.